Confirmatory Biopsy Outcomes in Patients with Grade Group 2 Prostate Cancer: Implications for Early Management - Riccardo Leni; Emily A. Vertosick; Nicole Liso; Oguz Akin; Sigrid V. Carlsson; Francesco Montorsi; Alberto Briganti; James A. Eastham; Samson W. Fine; Andrew J. Vickers; Behfar Ehdaie (European Urology Open Science)
Background and objective: Guideline recommendations regarding early management of grade group (GG) 2 prostate cancer with confirmatory biopsy (cBx) are not well established. Our aim was to determine which patients with GG 2 cancer should undergo cBx before treatment decision-making by evaluating the probability of downgrading to GG 1 or no cancer on cBx. Methods: This was a single-institution retrospective analysis of patients with GG 2 prostate cancer who underwent cBx. We modeled the probability of having no Gleason pattern 4 on cBx according to magnetic resonance imaging (MRI) Prostate Imaging-Reporting and Data System (PI-RADS) score, presence of extraprostatic extension (EPE) on MRI, total length of pattern 4 across all cores on initial Bx, and prostate-specific antigen (PSA) density. Key findings and limitations: Among 301 patients, 62 (21%) were downgraded to GG 1 and 23 (8%) had no cancer on cBx. For patients with nonsuspicious MRI findings (PI-RADS 1–3; n = 123), the probability of having no pattern 4 on CBx was 34%, 20%, and 11% for 1, 2, and 3 mm of pattern 4 at initial Bx. For PI-RADS 4–5 without EPE on MRI (n = 146), the corresponding probabilities were 18%, 10%, and 5%. Patients with EPE on MRI (n = 32) had low probability (<10%) of having no pattern 4 on cBx irrespective of pattern 4 on initial Bx. Results using a model based on PSA density followed a similar trend. After applying the model in a cohort of patients with GG 2 cancer who immediately underwent surgery (n = 2275), we estimated that two-thirds would be eligible for cBx before treatment using a probability threshold of 5–10% for avoiding immediate surgery. Conclusions and clinical implications: Patients with GG 2 prostate cancer, no evidence of EPE, and a few millimeters of pattern 4 should undergo cBx before proceeding to surgery. Further research should define the oncologic risk for such patients, refine the criteria for cBx in GG 2 disease, and assess methods for quantifying pattern 4 length in MRI-targeted cores. Patient summary: For patients with grade group (GG) 2 prostate cancer, we found that the amount of Gleason pattern 4 cancer in the initial biopsy, PSA (prostate-specific antigen) density, and MRI (magnetic resonance imaging) findings help to identify men who are likely to be downgraded to less aggressive GG 1 cancer or no cancer at all on a repeat confirmatory biopsy. We assessed these predictors in a group of patients with similar characteristics who underwent immediate surgery, and found that approximately two-thirds would benefit from a confirmatory biopsy.